2018
DOI: 10.1039/c8ob01768a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cycloaddition reactions of strained alkynes derived from 2,2′-dihydroxy-1,1′-biaryls

Abstract: A series of strained alkynes, based on the 2,2′-dihydroxy-1,1′-biaryl structure, were prepared in a short sequence from readily-available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A report by Xing et al 10 indicated that an effective pairing was a compound containing a methoxy group and a dimethylamino group para - to the ketone and aldehyde enone precursors respectively. Alkyne 15 6 was reacted under basic conditions with 4-dimethylaminobenzaldehyde to give 16 in good yield ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A report by Xing et al 10 indicated that an effective pairing was a compound containing a methoxy group and a dimethylamino group para - to the ketone and aldehyde enone precursors respectively. Alkyne 15 6 was reacted under basic conditions with 4-dimethylaminobenzaldehyde to give 16 in good yield ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We, 5–7 and others, 8 recently reported the synthesis of strained alkynes of general structure 7 , where X/Y = O, NH, NTs, 9 as reagents for copper-free cycloaddition reactions with azides (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%